(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The problem of transport is of great importance in companies and productive institutions, which pay great attention to it, to the problem of transport many types, including bilateral transport, triple transport and quadruple transport, which lags behind from one type to another by adding a variable, for example in the bilateral type uses the transfer of materials from storage sources to processing sources, either triple transport is by adding the variable of backward materials, while quadruple transport is by adding a variable type of vehicles, and in this research the problem of transport was studied The three-dimensional, which includes the transfer of various materials from storage sources to the requesting sources, and a case was studied in one of the Iraqi pharmaceutical companies and the transfer of three materials from two stores belonging to the company to medical savers was studied, where the problem of transportation was solved using linear programming and data analysis by the POM-QM program and the annual transportation costs were reduced by about 10 billion annually.